ЗАЩИТА ИНТЕРЕСОВ МАТЕРИ И РЕБЕНКА В СЕМЕЙНОМ ПРАВЕ (Journal of actual problems of jurisprudence, 2019)
Given article is dedicated to basic research the main principles of protecting motherhood and childhood in Family Law.Protection of motherhood and childhood is very relevant today because the future of the Republic of Kazakhstan depends on the careand government policy in the field of maternity and childhood.